Microstructural evolution and chemical corrosion of electron beam wire-feed additively manufactured AISI 304 stainless steel - Tarasov, S.Yu; Filippov, A.V.; Shamarin, N.N.; Fortuna, S.V.; Maier, G.G.; Kolubaev, E.A. (Journal of alloys and compounds, 2019)
Using an electron beam wire-feed additive manufacturing three sets of samples were obtained at different heat input levels. The samples contained different amounts of vermicular δ-ferrite that depended on the heat input value used. Chemical corrosion tests were carried out to find out that the corrosion resistance of a sample is determined by the δ-ferrite amount in it. High δ-ferrite content in the sample obtained at medium used heat input value caused enhanced corrosion in the Cr-depleted austenite grains. Otherwise, when using the maximum heat input the additively manufactured sample contained the minimum amount of δ-ferrite and demonstrated the highest corrosion resistance as well as formation of a cubic crystallographic texture. No such texture was found in samples grown at lower heat input values. In addition, no inter-granular corrosion induced open cracks have been observed on all samples after 90° angle flexural test. •Wire-feed electron beam additive manufactured samples were characterized.•The amount of vermicular ferrite correlated with the heat input value.•High heat input deposition resulted in formation of a crystallographic texture.•High-ferrite sample was characterized by intense intragranular corrosion.•Flexural test showed no intergranular corrosion.